Implementasi Metode Secure Hash Algorithm (SHA-1) Untuk Mendeteksi Orisinalitas File Audio - Rezky M. Nasution (Bulletin of Computer Science Research, 2022)
Audio file is a means of information from one person to another. Audio files are very vulnerable to fraud, eavesdropping or data theft by irresponsible parties. In order to maintain the security of audio files, this can be done by using cryptographic techniques. Cryptography is one of the data security methods that can be used to maintain data authenticity, data confidentiality, and the authenticity of data transmission. SHA stands for Secure Hash Algorithm is a standard hash function published by NIST (National Institute of Standards and Technology). SHA is published with a digest size of 512 bits. SHA-1 will output 160 bits of the string and the output string is called a message digest. The length of the message digest can range from 160 to 512 bits depending on the algorithm. This study describes the security process for detecting the authenticity of audio files using the SHA-1 method in the form of detection so that confidential audio sent via public telecommunications cannot be changed or modified by unauthorized persons or unauthorized persons. This is done as an effort to minimize acts of fraud, hoaxes, or misuse of audio files.